Analysis Slope Stability And Seepage Logung Dam – Kudus Central Java - Muhammad Taufiq; Wahyu Kurniawan (International Conference on Coastal and Delta Areas, 2017)
Logung Dam is located in Dukuh Slalang, Tanjungrejo Village, Jekulo District and Dukuh Sintru, Kandangmas Village, Dawe District. Logung Dam has an area of inundation of 144.06 ha and a normal catch of 20,150,000 m3. This analysis is to know the safety of the slope and seepage with the result of the approaching analysis so that it can give it to the dam. Zone analysis conducted with the location of the dam, physical testing of the material in the clay laboratory (zone 1), sand (zone 2), random (zone 4), show the results indicating the soil as the analysis material meets the dam requirements. Analyze the data required by the planner's consultant in the laboratory. Soil parameter data used in PLAXIS 8.6 and Geostudio 2007 programs: cohesion, c; Sliding angle in soil, φ; Slope angle,  ;  nd  he  eigh  o   he  ol me o  land,  ;  od l s o  elas ici  ,  ;  ermea ili  ,  ;  nd poisson ra io,  rom soil parame er da a can  e  o nd nialai cohesion  c         , shear  orce  φ                 , slope angle        :   upstream, 1:35 do ns ream and  ol me  eigh  Soil           6  rom  L XIS da a a   he  al e o  deformation = 26.46 m, active pore pressure = -927.61 m, effective soil voltage -2.70x10-3 kN / m2; down slope safety = 1, 26 and seepage = 46,41x10-3 From geostudio program can obtain upstream slope safety factor = 1.41, downhill slope security = 1.23 and seepage = 63.30x 10-3.Air dam safety analysis to normal safe, For seepage safety by grouting or injection of cement on the ground beneath the foundation along the dam. Keywords: Analysis, Security Factor, Plaxis and Geostudio